Faktor-Faktor Yang Memengaruhi Penganggaran Berbasis Kinerja (Performance Based Budgeting) Pada Pemerintah Kabupaten Jember - Abdul Ghofur; Muhammad Firdaus; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to study the effect of commitment, leadership style, reward, punishment and quality of human resources on performance-based budgeting (performancebased budgeting) in the Jember Regency Government in 2019. Data processing methods use multiple analysis with the help of SPSS analysis tool version 21. Research results demonstrate accounting commitment, leadership style, reward, punishment and quality of human resources for performance-based budgeting. Partially, commitment accounting, leadership style, punishment and quality of human resources are not related to performance-based budgeting, while awards have a significant and positive effect on performance-based budgeting.